The Talking Sticks Method Enhances the Skills of Community Empowerment Cadres in the Early Prevention of Stunting Incidents - Sudarman, Yulianus; Tampake, Rina; Lewa, Abd Farid; Efendi, Fauzan (Jurnal Bidan Cerdas, 2025)
Introduction: In 2022, the World Health Organization reported 148.1 million children under five suffering from stunting, reflecting poor nutritional patterns globally. The WHO targets a maximum stunting prevalence of 20%. Indonesia, with a stunting rate of 31.8% in 2020, ranks second in Southeast Asia. In Central Sulawesi, 34% of toddlers are malnourished, as observed in a survey at Pagimana Health Center, which covers 24 villages and includes 135 community health workers.  Purpose: This study aims to evaluate the impact of the talking stick intervention on improving Posyandu cadres' knowledge, attitudes, and behaviors in providing stunting counseling. Research Method:An experimental research design with a quantitative approach was used,  specifically a Pre-Experimental Design with a One Group Pretest-Posttest Design. The sample included 88 Posyandu cadres. Data analysis involved normality tests and hypothesis testing using t-tests to assess the effectiveness of the intervention. Results: The paired t-test revealed significant differences between the results of the pre-test, post-test 1, and post-test 2, with a p-value of 0.00, indicating a significant impact of the talking stick method on the knowledge of community empowerment cadres in the early prevention of stunting. Conclusion: The talking stick intervention effectively enhances Posyandu cadres' knowledge, attitudes, and actions, proving valuable for early stunting prevention in Pagimana District, Banggai Regency.